Experimental Study of Thermo-Physical Properties of Nanofluids Based on γ-Fe2O3 Nanoparticles for Heat Transfer Applications. Issue 17 (22nd November 2017) - Huminic, Gabriela; Huminic, Angel; Dumitrache, Florian; Fleaca, Claudiu; Morjan, Ion
ABSTRACT: The main goal of the present study was to prepare and also to investigate the effects of both temperature and weight concentration on the thermo-physical properties of γ-Fe2 O3 /water nanofluids. The γ-Fe2 O3 nanoparticles were synthesized by laser pyrolysis technique and characterized using TEM, XRD, and EDX techniques. Thermal conductivity, viscosity and surface tension of γ-Fe2 O3 /water nanofluids were investigated within the range of the temperature of 20°C to 70°C for various weight concentrations of nanoparticles (0.5, 1.0, 2.0, and 4.0 wt%). The experimental results show that the thermal conductivity ratio is much higher than of thermal conductivity of base fluid. Thus, the relative thermal conductivity was 59% for a concentration of 4.0 wt% and a temperature of 50°C. Also, it has been observed that the influence of weight concentration of nanoparticles on viscosity was lower at temperatures over 55°C. At standard temperature of 25°C and 2.0 wt.% concentration of nanoparticles, the relative dynamic viscosity was 5.61%. Experimental results show that the surface tension increases with increase of weight concentrations and decreases with increase of temperatures. For a temperature of 70°C and 2.0 wt.% concentration of nanoparticles, the relative surface tension was 46%. The experimental results were compared with data available in literature.